2022
DOI: 10.3390/biomedicines10102521
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Results of Severe Intraepithelial Squamous Cell Lesions and Preinvasive Cervical Cancer Phototheranostics in Women of Reproductive Age

Abstract: (1) Purpose: To investigate the efficacy and safety of using PDT in the treatment of severe intraepithelial squamous lesions of the cervix and preinvasive cervical cancer associated with HPV in women of reproductive age. (2) Methods: The examination and treatment of 45 patients aged 22–49 years with morphologically confirmed HPV-associated cervical intraepithelial neoplasia of a severe degree (17 patients) and preinvasive cervical cancer (28 patients) were performed. All patients underwent PDT of the cervix us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Several studies have shown that treatment with ablation has no significant adverse effects on pregnancy outcomes, including preterm birth and PROM. 22 , 23 Although it is important to protect fertility, reducing the persistence or recurrence of precancerous lesions is equally important. Some research suggests that persistence of HPV infection and positive endocervical margins are risk factors for the persistence or recurrence of CIN, and there is no significant association with the type of therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that treatment with ablation has no significant adverse effects on pregnancy outcomes, including preterm birth and PROM. 22 , 23 Although it is important to protect fertility, reducing the persistence or recurrence of precancerous lesions is equally important. Some research suggests that persistence of HPV infection and positive endocervical margins are risk factors for the persistence or recurrence of CIN, and there is no significant association with the type of therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Another approach to optimizing PDT treatment parameters on tumor tissue, including spot diameter and radiation fluence, was implemented through numerical simulation of laser radiation propagation with varying fluence and spot diameter in cervical tissue and the monitoring of PS photobleaching and hemoglobin oxygenation degree on phantoms (optical models) imitating the optical properties of cervical tumor tissue [88]. Based on an analysis of all the data obtained and considering the depth of the cervical lesion established through histological examination, the most appropriate laser radiation energy parameters for PDT (spot diameter and radiation fluence) for cervical dysplasia and cancer in 107 patients were determined, thus minimizing side effects and preventing disease progression and recurrence [13,14,52].…”
Section: Combined Methods Of Fluorescence Imaging and Diffuse Reflect...mentioning
confidence: 99%
“…This approach enabled the PDT process to be monitored at all stages of treatment. At Ce6 concentrations of 0.8-1.2 mg/kg, fluorescence images of the cervix exhibited well-defined contrast between pathologic and normal surrounding tissue, allowing for the assessment of PS distribution over the entire measured area with a resolution of 1 mm [13,14,52]. In a separate study, fluorescence diagnostics and 5-ALA-and hexyl aminolevulinate-PDT (HAL-PDT) were employed to examine cervical dysplasia and vulvar leukoplakia in both continuous and pulsed laser irradiation modes.…”
Section: Fluorescence Imagingmentioning
confidence: 99%
See 1 more Smart Citation